Financial Literacy Movement: Student Financial Education Strategy through Partnerships between Universities and Financial Institutions - Henry Dunan Pardede; Hengki Mangiring Parulian Simarmata; Erwin Sirait; Natalia Pransiska Silaen; Andriano Simarmata (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
The low level of financial literacy among students is an important concern in the increasingly complex digital economy era. To address these issues, this Community Service activity promotes the theme "Financial Literacy Movement 2025," which aims to enhance students' understanding of personal financial management, budget planning, and the prudent use of digital financial services. The activity was held on June 11, 2025, at 10.00 WIB at the Hall of Murni Teguh University PSDKU Pematangsiantar, involving 50 students from various study programs in Pematangsiantar. This activity represents a form of cooperation between Murni Teguh University (PTSDKU Pematangsiantar) and PT Pegadaian Parluasan Branch. The implementation method was carried out in the form of interactive seminars and question and answer discussions, which presented two speakers: Mr. Henry Dunan Pardede, S.P., M.M. (Academic) and Mr. Eko Syahri Iskandar (Head of the UPC Pegadaian Unit Parluasan Branch). At the end of the activity, participants participated in a lucky draw session as a form of appreciation and motivation. The results of the activity showed high enthusiasm and increased understanding among participants of the importance of financial literacy in student life. This activity is a strategic step in shaping a young generation who are financially wise and able to make smart economic decisions.